Information and Management Engineering International Conference, ICCIC 2011, Wuhan, China, September 17-18, 2011. Proceedings, Part V - Zhu, Min.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This six-volume-set (CCIS 231, 232, 233, 234, 235, 236) constitutes the refereed proceedings of the International Conference on Computing, Information and Control, ICCIC 2011, held in Wuhan, China, in September 2011. The papers are organized in two volumes on Innovative Computing and Information (CCIS 231 and 232), two volumes on Computing and Intelligent Systems (CCIS 233 and 234), and in two volumes on Information and Management Engineering (CCIS 235 and 236).
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Software Engineering